2003
DOI: 10.1103/physrevb.68.094101
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure x-ray diffraction and Raman spectroscopic studies of the tetragonal spinelCoFe2O4

Abstract: In situ x-ray diffraction and Raman spectroscopy have been carried out to pressures of 93.6 and 63.2 GPa, respectively, to explore the pressure-induced phase transformation of CoFe 2 O 4 spinel. CoFe 2 O 4 adopts a distorted tetragonal spinel structure at one atmosphere. At a pressure of ϳ32.5 GPa, both x-ray diffraction and Raman spectroscopy indicate that CoFe 2 O 4 transforms to the orthorhombic CaFe 2 O 4 structure, which remains stable to at least 93.6 GPa. The bulk modulus (K 0 ) of the tetragonal and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
43
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 25 publications
(16 reference statements)
8
43
1
Order By: Relevance
“…[18] The value of ϒ i of of 0.42 for the 703 cm −1 mode is taken on the basis of the value for CoFe 2 O 4 obtained from high-pressure Raman studies. [19] The two compounds matches well in structural and other properties and, hence, to the first approximation we assume the Gruneisen parameter for the two compounds have similar values. Here a represents difference in lattice parameter of the nanoparticles compared to the bulk value (a 0 ) and ω i denotes Raman mode position.…”
Section: Resultsmentioning
confidence: 99%
“…[18] The value of ϒ i of of 0.42 for the 703 cm −1 mode is taken on the basis of the value for CoFe 2 O 4 obtained from high-pressure Raman studies. [19] The two compounds matches well in structural and other properties and, hence, to the first approximation we assume the Gruneisen parameter for the two compounds have similar values. Here a represents difference in lattice parameter of the nanoparticles compared to the bulk value (a 0 ) and ω i denotes Raman mode position.…”
Section: Resultsmentioning
confidence: 99%
“…As for CoFe 2 O 4 , there are five Raman active modes (Ag þ Eg + 3F 2g ) and four infrared modes (4F 1u ) [22,23]. Figure 4 shows the measured Raman spectra from 1000 to 100 cm À1 .…”
Section: Resultsmentioning
confidence: 99%
“…In a similar way, MCr 2 O 4 spinels with M = Mg, Mn, and Zn are theoretically predicted to decompose above 19 GPa, 23 GPa, and 34 GPa, respectively [295]. However, a recent study has shown that ZnAl 2 O 4 is stable in the cubic spinel structure up to 43 GPa [296] [297,298].…”
Section: Ab 2 X 4 Compoundsmentioning
confidence: 90%